Outcome of Rhabdomyosarcoma in First Year of Life: Children's Cancer Hospital 57357 Egypt. (25th July 2013) - El Nadi, Enas; Moussa, Emad A. H.; Zekri, Wael; Taha, Hala; Yones, Alaa; Zaghloul, Mohamed Saad; El Wakeel, Madeeha; Labib, Rania M.
Abstract : Background . Rhabdomyosarcoma (RMS) is the most common soft-tissue sarcoma in children. Fifty percent of RMS cases occur in the first 10 years of life and less commonly in infants younger than one-year old. These infants require adapted multimodality treatment approaches. Patients and Methods . We analyzed patients' characteristics, treatment modalities, and the outcome for RMS infants treated at Children's Cancer Hospital Egypt (CCHE) between July 2007 and December 2010 and compared them to patients above one year treated on the same protocol. Results . Out of the 126 RMS treated during this period, 18 were below the age of one year. The male: female ratio was 1.25 : 1. The median age at diagnosis was 0.7 ± 0.2 years. Most of the cases (27.8%) were presented in head and neck regions. The estimated 4-years failure-free survival and overall survival for infants were 49 ± 12% and 70 ± 12%, respectively. These failure-free survival rate and overall survival rate did not differ from those for older patients (P = 0.2 ). Conclusion . Infants with RMS are a unique group of RMS who needs special concerns in tailoring treatment in addition to concerns regarding toxicity and morbidity in infants.